Subalternidades e fronteiras culturais: embates nos territórios e extrativistas no litoral sergipano - Silva, Heberty Ruan da Conceição (2024)
Extractive communities along the Sergipe coast share a post-colonial present marked by cultural, identity, and territorial conflicts, resulting from multiple tensions caused by urban pressure on traditional cultures and coastal ecosystems. The municipality of Barra dos Coqueiros has emerged as a key site for these conflicts due to recent metropolitan expansion, driven by real estate speculation and the development of numerous exclusive housing projects. Aware of this issue, the goal of this dissertation is to understand the process of forming new cultural boundaries in Barra dos Coqueiros within the context of urban expansion into traditional extractive territories. The decolonial approach, centered on valuing the perceptions and experiences of the subaltern, as well as describing their lived worlds, was established as the primary focus for interpreting the post-colonial condition of extractive communities. This research engages with authors (Mignolo, 2017; Haesbaert, 2021; Porto-Gonçalves, 2005; Homma, 1990; Martins, 2021; Almeida, 2005) to understand the colonial legacy, the geo-history of coastal occupation in Sergipe, the productive transversality of extractivism, the submission to urban expansion, and the resulting cultural clashes. The methodological approach followed qualitative research, which allows for an integrated analysis of the phenomenon, combining a phenomenological approach with decolonial narratives. The adopted procedures included bibliographic research, document analysis with content analysis, and fieldwork for primary data collection. The findings reveal that cultural boundaries, supported by geo-historical heritage, manifest in lived territories and landscapes. With the arrival of the ‘other’—new residents living in vertical and horizontal condominiums over the lived territories of the ‘one’—extractive groups, particularly mangaba collectors, conflicts have intensified in the border zone. The persistence, transformation, and resistance of these dynamics are evident, with future developments indicated by the gaps in these clashes.